Multi-omics analyses reveal interactions between GREM1+ fibroblasts and SPP1+ macrophages in gastric cancer - Lupeng Qiu; Xiao Zhao; Sheng Yao; Yang Fei; Yixin Gong; Zishan Zhou; Shunchang Jiao; Jianming Xu (npj Precision Oncology)
Abstract Gastric cancer (GC) is among the most lethal human malignancies with limited treatment options. Cell-cell interactions within the tumor microenvironment (TME) can promote tumor growth, yet their therapeutic value has not been fully explored. Here, bulk RNA-seq, single-cell RNA sequencing (scRNA-seq), and spatial transcriptomics (ST) were integrated to analyze the heterogeneity of GC microenvironment. Tumor-specific GREM1+ fibroblasts and SPP1+ macrophages were significantly enriched in GC tissues and were involved in immunosuppression, inflammation regulation, and tumor progression. We then indicated that GREM1+ fibroblasts and SPP1+ macrophages were positively correlated in 12 independent GC datasets and validated their close localization by multiplex immunohistochemistry staining and spatial transcriptomics. Patients with both high GREM1+ fibroblasts and SPP1+ macrophages exhibited significantly shorter OS and showed enrichment of tumor-associated pathways. Our results demonstrated the complex interactions between GREM1+ fibroblasts and SPP1+ macrophages, which may serve as a potential therapeutic target for future treatment of GC.